The interplay of customer experience and commitment. Issue 2 (10th April 2017) - Keiningham, Timothy; Ball, Joan; Benoit (née Moeller), Sabine; Bruce, Helen L.; Buoye, Alexander; Dzenkovska, Julija; Nasr, Linda; Ou, Yi-Chun; Zaki, Mohamed
Abstract : Purpose: This research aims to better understand customer experience, as it relates to customer commitment and provides a framework for future research into the intersection of these emerging streams of research. Design/methodology/approach: This research contributes to theoretical and practical perspectives on customer experience and its measurement by integrating extant literature with customer commitment and customer satisfaction literature. Findings: The breadth of the domains that encompass customer experience – cognitive, emotional, physical, sensorial and social – makes simplistic metrics impossible for gauging the entirety of customers' experiences. These findings provide strong support of the need for new research into customer experience and customer commitment. Practical implications: Given the complexity of customer experience, managers are unlikely to track and manage all relevant elements of the concept. This research provides a framework identifying empirically the most salient attributes of customer experience with particular emphasis on those elements that enhance commitment. This offers insight into service design to correspond with specific commitment and experience dimensions. Originality/value: This research is the first to examine the customer experience as it relates to customer commitment – a key factor in customer loyalty, positive word of mouth and other desired outcomes for managers and marketers. This paper provides a framework for future research into these emerging topics.